Experts' opinions on terminology for complementary and integrative medicine - a qualitative study with leading experts - Holmberg Christine; Brinkhaus Benno; Witt Claudia (BMC, 2012)
Abstract Background Integrative medicine (IM) is currently the most commonly used term to describe the integration of complementary and alternative medicine (CAM) into conventional medicine. In the definitions of IM the most important feature is the focus on evidence as crucial factor for therapeutic decision-making. However, there are discussions on the term "integrative medicine" with the most notable critique from within CAM that it describes the integration of complementary methods into conventional institutions and into a "conventional framework of thinking". The aim of this qualitative study was to understand the thoughts of leading experts on IM and on the scientific debate in the field as well as their personal opinions about terminology in general. Methods We have conducted semi-standardized interviews with ten leading experts in the field of CAM and integrative medicine in the USA, England, and Germany, who have had leading positions at medical schools or the NIH in 2010 and 2011. Interviews were recorded, transcribed and analyzed using content analysis with the qualitative analysis software maxqda. Results Overall the current terminology was seen as a problem, although most experts agreed that the term "integrative medicine" (IM) described well what they do or they think is useful for medical care. The terminology debate was discussed from four perspectives: 1) from the perspective of medical practice, 2) from the perspective of research, 3) from the perspective of public relations, and 4) from the perspective of health care delivery. These perspectives may be used to evaluate the appropriateness of different terms in use in the field. When interviewees discussed the terminology question, they also discussed the type of health care system they envisioned. Such reflections led the interviewees to caution about too narrow a focus on the terminology question. The question of naming was one about influencing and changing medicine. Conclusion The discussion of the experts demonstrated that the discussion about terminology is an important debate about the shaping of medicine. The experts discussed terminology in the light of "how health care systems" should look like in the future.